Determination of DL-Methionine with Electro-chemiluminescence Molecularly Imprinting Method - Du, Zhen; Fan, Chenling (Asian Journal of Chemistry, 2014)
In order to establish a novel EC-MIP method in the determination of DL-methionine in human urine, a carbon electrode of [Ru(bpy)3]2+ was modified with the molecular imprinting polymers electro-deposited with the sol-gel method. The abilities of the electrochemical and electro-chemiluminescence characteristics of the above electrode were then investigated with the quantitative determination of dL-methionine in human urine. The method exhibited the high sensitivity and excellent selectivity towards DL-methionine. With the optimized conditions, the linear range of dL-methionine was from 1 × 10-11 mol/L to 1 × 10-8 mol/L, with the LOD as 2.6 × 10-12 mol/L. This method could be successfully applied to the determination of dL-methionine in human urine samples for the precaution of certain diseases.